Syntheses, crystal structures, topology and dual electronic behaviors of a family of amine-templated three- dimensional zinc-organophosphonate hybrid solids - Rom, Tanmay; Kumar, Nikhil; Agrawal, Anant; Gaur, Anurag; Paul, Avijit Kumar (Elsevier BV, 2022)
Three new inorganic-organic hybrid zinc organodiphosphonate compounds, [H 2 TEMED][Zn 3 (hedp) 2 ] ( 1 ), [H 2 TEPA][Zn 6 (Hhedp) 2 (hedp) 2 ] center dot 2H 2 O ( 2 ) and [H 2 DETA] 2 [Zn 12 (Hhedp) 4 (hedp) 4 ] center dot 3H 2 O ( 3 ) (H 4 hedp = 1-hydroxyethane 1,1-diphosphonic acid, TEMED = N,N,N',N'-tetramethylethylenediamine, TEPA = tetraethylenepentamine and DETA = diethylenetriamine) have been synthesized by employing the variable amine-templated hydrothermal strategy. All the compounds are characterized and analyzed by PXRD, FT-IR, TGA, SEM and EDAX studies. Single crystal x-ray diffraction experiments reveal that the compounds 1 -3 have formed interconnected 4-T, 8-T and 12-T open ring three-dimensional framework structure through the alternate connection of zinc ions and diphosphonate ligands. Topological analysis study displays compound 1 adopts (4.5.7 2 .8.9)(4.7.8)(5 2 .7 2 .8 2 )(5 2 .7) net topology whereas compounds 2 and 3 show ILEHUD (4.5.6.8 3 )(4.6.8)(5 2 .6.8 3 )(5 2 .8) net topology, even though the observed asymmetric units are dissimilar in case of 2 and 3 . The UV-visible spectroscopic studies recommend the compounds as wide band-gap semiconducting materials. The observed dielectric permittivity of the compounds are considerably high ( epsilon' similar to 100) at room temperature. The electrochemical performance tests indicate that compound 3 exhibit a high specific capacitance of 216 F g -1 at 1 A g -1 along with an excellent cycle stability of 79.6 % even after 50 0 0 cycles at 5 A g -1 in the 6 M KOH solution while compound 1 and 2 possess specific capacitance values of 164 and 170 F g -1 with cycling retention of 68.42 % and 57.82 %, respectively. Such high-performance supercapacitance behavior in amine templated framework is noteworthy.